Techno-Economic Study of Solar Energy Implementation in Hospitals in Malaysia - Siow, Chun Lim; Leao, Hen Yew; Panneerselvam, Anandan (International Journal of Energy Economics and Policy, 2025)
As the demand for energy in hospitals continues to increase, there is a favorable opportunity for Malaysia to embrace solar energy. This research paper examines the potential of solar photovoltaic (PV) systems in hospitals by evaluating factors such as payback period, return on investment (ROI), and savings. A total of 42 hospitals in Malaysia were selected for the study and categorized as large, medium, and small based on their bed capacity. Initially, a background analysis of these hospitals is conducted, followed by an estimation of their rooftop area. Subsequently, the energy consumption of the hospitals is determined using the building energy index approach. The PVsyst software is utilized to simulate the energy output generated by solar PV systems. The findings reveal that two hospitals can fully meet their energy demand through solar energy generation, while the remaining 40 hospitals achieve average savings of 38.76%, 37.48%, and 52.58% for large, medium, and small hospitals, respectively. These results underscore the considerable benefits of implementing solar PV systems in a significant portion of the hospitals, with some being able to cover their entire energy requirements. In conclusion, this study provides valuable insights into the viability of solar PV systems in Malaysian hospitals.